Overview of the History of the Debate about Theological Education - Wingate, Andrew (International review of mission, 2005)
The article reflects on developments in theological education over the last thirty years. The author draws on his extensive experience during these years, primarily within India and Britain. The context has changed greatly in this period, globally and locally, within the wider world and within the church. This makes questions of mission and ministry very different today. Mission is now accepted as being a critical task within the churches of the West, and not just in what used to be seen as “the mission field”. Major issues are discussed: the nature of contextuality; the use of the Bible; questions of breadth as well as depth of content; the place of mission within any programme; educational methodology (including the use of information technology); questions of access, including the inclusion of lay people and women; the development of varied modes of training. Fundamental to all these is an affirmation that theological education is never finished; it is a lifelong process. Also central is the need to consider the purpose of theological education; various key issues are raised. Theological education is affirmed as education for change, and involves the integration of tradition, context, experience and skills.